Human Will in The Stories of Jack London and Khayriddin Sultan - Elboyeva Madina Botirovna (Genius Journals, 2023)
This article analyzes the mutual commonality of the creative visions of the great English writer Jack London and the well-known writer of new Uzbek literature, Khayriddin Sultan, the interpretations of universal problems based on poetic allusions, heroic endeavors, the thoughts and experiences of their artistic heroes, their thoughts about the world and existence
Keywords: poetic allusions; psychological interpretations; heroic endeavors